2008
DOI: 10.1063/1.3035904
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics of the O+OH→H+O2 reaction at low temperatures

Abstract: We report quantum dynamics calculations of the O + OH --> H + O(2) reaction on two different representations of the electronic ground state potential energy surface (PES) using a time-independent quantum formalism based on hyperspherical coordinates. Calculations show that several excited vibrational levels of the product O(2) molecule are populated in the reaction. Rate coefficients evaluated using both PESs were found to be very sensitive to the energy resolution of the reaction probability, especially at te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…This opened the possibility that the O 2 abundance in cooler clouds would be much lower than predicted by the above astrochemical models. However, more elaborate quantum mechanical calculations by Quémener et al (2008) showed a relatively weak temperature dependence, and a rate coefficient at 10 K that is 70 times larger than predicted by Xu et al (2007).…”
Section: Chemistry Of Oxygen In Dense Interstellar Cloudsmentioning
confidence: 99%
“…This opened the possibility that the O 2 abundance in cooler clouds would be much lower than predicted by the above astrochemical models. However, more elaborate quantum mechanical calculations by Quémener et al (2008) showed a relatively weak temperature dependence, and a rate coefficient at 10 K that is 70 times larger than predicted by Xu et al (2007).…”
Section: Chemistry Of Oxygen In Dense Interstellar Cloudsmentioning
confidence: 99%
“…In the ultracold regime, a single partial wave (i.e., the l=0 angular momentum partial wave or s-wave for bosons and distinguishable particles, and l=1 or p-wave for identical fermions) contributes to the scattering cross sections and the ultracold reaction rate coefficients obey the well known Bethe-Wigner threshold laws [74][75][76][77][78]. For exoergic processes these rate coefficients approach finite measurable values comparable to or even larger than their values at thermal energies [64][65][66][67][68][79][80][81][82][83]. The tiny kinetic energy associated with ultracold collisions makes them amenable to control via external electric or magnetic fields [69][70][71][72][84][85][86][87].…”
Section: Introductionmentioning
confidence: 99%
“…Although DMBE IV is likely the most widely used due to being remarkably adequate 42 for calculating reaction rate constants, a spline interpolant to nearly 18 000 ab initio points 43 calculated at the internally contracted multireference configuration interaction 44 level with the Davidson correction and an augmented quadruplezeta correlation consistent basis set [45][46][47] (MRCI+Q/AVQZ) has emerged. Many theoretical investigations 40,42,[48][49][50][51][52][53][54] of the O + OH rate constant below 50 K have utilized the latter, hereinafter named XXZLG, 55 or both this and DMBE IV. Experimentally, the O + OH reaction has also been much studied, [56][57][58] and rate constants recommended.…”
Section: Introductionmentioning
confidence: 99%